2013
DOI: 10.1242/jcs.123810
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin pathway represses let-7 microRNAs expression via transactivation of Lin28 to augment breast cancer stem cell expansion

Abstract: SummaryWnt signalling through b-catenin and the lymphoid-enhancing factor 1/T-cell factor (LEF1/TCF) family of transcription factors maintains stem cell properties in both normal and malignant tissues; however, the underlying molecular pathway involved in this process has not been completely defined. Using a microRNA microarray screening assay, we identified let-7 miRNAs as downstream targets of the Wnt-b-catenin pathway. Expression studies indicated that the Wnt-b-catenin pathway suppresses mature let-7 miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 56 publications
5
91
1
2
Order By: Relevance
“…As a previous report concluded that activated Wnt signaling up-regulates Lin28a in breast cancer cells (Cai et al 2013), we determined the levels of Lin28a in the Apc Min/+ tumors and failed to detect expression (Supplemental Fig. 4A).…”
Section: Lin28 Promotes Proliferation and Inhibits Differentiation Ofmentioning
confidence: 97%
“…As a previous report concluded that activated Wnt signaling up-regulates Lin28a in breast cancer cells (Cai et al 2013), we determined the levels of Lin28a in the Apc Min/+ tumors and failed to detect expression (Supplemental Fig. 4A).…”
Section: Lin28 Promotes Proliferation and Inhibits Differentiation Ofmentioning
confidence: 97%
“…It is possible that the conserved tumor suppressor function of the let-7 microRNA (57, 58) may in part reflect conserved roles in regulating LIT-1/POP-1/APR-1 asymmetry and hence promoting asymmetric (nonproliferative) cell division. Similarly, the conserved role for LIN-28 in promoting stem cell fate in diverse contexts, including cancer (17,59,60), may reflect a general activity for LIN-28 in opposing LIT-1/POP-1/APR-1 stem cell division asymmetry.…”
Section: Stage-specific Heterochronic Gene Activities Promoting Seam mentioning
confidence: 99%
“…This finding suggests that LIN28B a novel direct downstream target gene of the Wnt/b-catenin pathway. Interestingly, a recent research revealed that LEF1, another effector of Wnt/b-catenin pathway, could activate LIN28A via direct binding to the LIN28A promoter (27). This report provided compelling evidence that both LIN28A and LIN28B were direct target genes of the Wnt/b-catenin pathway.…”
Section: Discussionmentioning
confidence: 63%
“…In fact, it has been reported that LIN28A/LIN28B can promote transformation by repressing let-7 miRNAs, and that activation of LIN28A/LIN28B occurs in many different human tumors with a frequency of approximately 15% (23,24). Recent studies have also suggested that LIN28 plays an important role in the maintenance of CSCs (25,26) and Wnt signaling could directly activate LIN28 to augment breast cancer stem cell expansion (27).…”
Section: Introductionmentioning
confidence: 99%